ATTITUDES TOWARD BILINGUALISM: EVIDENCE FROM DIFFERENT IRANIAN ETHNO-LINGUISTIC COHORTS - Modirkhamene, Sima (Sustainable Multilingualism / Darnioji daugiakalbystė, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*292.99px); top: calc(var(–scale-factor)*75.38px); font-size: calc(var(–scale-factor)*6.96px); font-family: sans-serif; transform: scaleX(1.15698);" role="presentation">http://dx.doi.org/10.7220/2335-2027.5.2 In multilingual settings where several heritage languages co-exist, the gradual process of assimilation may lead to loss of minority languages. In other words, in such settings, with no provision made for the individuals of the specific heritage languages to learn to read and write their first language (L1), language shift is accelerated and is almost sure to take place. It is therefore urgent to scrutinize the problem from different perspectives and to propose recommendations to maintain heritage language(s). One such consideration is what speakers of different languages in multilingual settings think about their linguistic status and language maintenance. Accordingly, this study provided quantitative and qualitative data on the attitudes of a random sample (N=224) of Iranians from different layers of society (i.e., universities, schools, and families) toward bilingualism. Data was collected through: (a) a tailor-made questionnaire that measured participants’ attitudes and (b) further follow up interviews conducted with 20% of the participants. The findings indicated that the representative samples appreciated the opportunity to learn two or more languages and perceived bilingual abilities as being to ones’ advantage in his/her future life. However, the positive tendency towards bilingualism varied significantly among cohorts forming diffident layers of the society. Results are interpreted in relation to the possible reconsideration of language policy in Iran.